Nepotism in the Story of Prophet Musa and Harun in the Qur’an: A Thematic Study - Arif Budiman; Ahmad Zuhri; Mardian Idris Harahap (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes the practice of nepotism in the relationship between Musa and Harun in the Qur’an from an Islamic kinship perspective supported by divine legitimacy. The main focus of this study is to analyze key verses in the Qur’an related to nepotism (the granting of power in kinship) in the story of Musa and Harun. Through qualitative methods and maudhu’i (thematic) interpretation with a content analysis approach to explore the thoughts of exegetes (mufassir) regarding the relationship between Musa and Harun both in lineage, religion, da’wah and leadership. The results chapter of this study discusses in depth three main indicators of nepotism in the story of Musa and Harun in the Qur’an. First, the intention or purpose underlying Musa’ request to give Aaron a position. Second, Harun’s superiority or capability as a candidate proposed by Musa to Allah SWT. Third, divine legitimacy or conformity with sharia values (justice). The results of this study indicate that the granting of power in kinship (nepotism) found in the story of Musa and Harun is positive because it is based on the goal of the welfare of the people and the excellence of Aaron which Allah recorded in the Qur’an especially in the field of fashahah and the granting of this position is not only in accordance with the value of justice but also received direct approval from Allah SWT. This study is expected to contribute to the development of Islamic leadership and become a reference for further studies in the field of politics or Islamic leadership.